MANAGEMENT OF THE ORGANIZATION’S FINANCES IN CONDITIONS OF UNCERTAINTY - Dmitrii TRACH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The market economy of management introduces significant changes in the understanding of the role and responsibility of state institutions and economic entities in the development of socio-economic processes and their effectiveness. Despite the huge role of state institutions, the real sector of the economy is the main contributor to state budget revenues. Its quality depends on the financial condition of economic entities, which, in turn, depends on the quality of financial management, the improvement of which in the conditions of external uncertainty is extremely important.